MANAJEMEN PERPUSTAKAAN INSTITUT AGAMA ISLAM AL-ZAYTUN INDONESIA DALAM MENINGKATKAN LITERASI DAKWAH MAHASISWA FAKULTAS DAKWAH ANGKATAN 10 - Sumarno; Sobirin; Suryandari, Meity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The library has a strategic role as an information center in supporting the development of students' da'wah literacy. This study aims to analyze the library management of Institut Agama Islam Al-Zaytun Indonesia in enhancing the da'wah literacy of the 10th cohort students of the Faculty of Da'wah and to evaluate the utilization of the library in supporting literacy-based da'wah activities. The research employs a qualitative descriptive approach with analysis based on the POAC management theory (Planning, Organizing, Actuating, Controlling). Data were collected through observation, in-depth interviews with library managers and students, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that library management has systematically implemented the POAC functions in managing da'wah literacy programs. The utilization of the library contributes to enhancing students' da'wah literacy, encompassing mastery of Islamic teachings, communication skills, and the ability to adapt to technology. However, obstacles remain, such as low student visitation rates, requiring innovative strategies to increase student engagement in literacy activities. These findings underscore the importance of synergy between adaptive library management and the needs of da'wah literacy in the digital era.